Assessment of Tolerance in Selected Onion Genotypes to Thrips Population in Bahawalpur, Pakistan: Screening of Onion Genotypes Against Onion Thrips - Muhammad Aqib; Muhammad Waqar Hassan; Liaqat Ali; Ghulam Sarwar (Biological Sciences - PJSIR, 2025)
Onion thrips are one of the most significant pests of onion. Study was conducted during rabi season of 2022-23 to screen seven onion genotypes namely Nasarpuri, Phulkara, Sultan, VRIO-2, VRIO- 3, VRIO-8 and VRIO-15 against thrips at experimental farm of Islamia University of Bahawalpur following randomized complete block design. Results showed maximum thrips on Nasarpuri (29.78) followed by 29.60 and 29.17 on VRIO-2 and Sultan respectively. Least population was on VRIO-8, VRIO-15 and Phulkara with 16.86, 15.40 and 13.35 thrips respectively. Study of plant morphological traits showed plant height, number of leaves per plant and leaf width was positively associated with thrips population. Among physiological traits more thrips were negatively associated with relative chlorophyll content, linear electron flow (LEF) and photosystem2 (Phi2) but positively associated with NPQt or energy dissipation. There was weak positive correlation between thrips population and bulb yield which instead showed tolerance against thrips attack in those genotypes particularly for Nasarpuri, VRIO-2 and Sultan. On the other genotypes VRIO-8, VRIO-15 and Phulkara showed resistance to thrips abundance. Knowledge about tolerant and resistant genotypes is important and can be utilized in future breeding programs for development of promising onion genotypes.